The Role of Ethical Climate in the Relationship between Task Conflict and Counterproductive Behavior - Samara Monteiro Pereira; Juliana Barreiros Porto (Journal of Work and Organizational Psychology)

(untitled)
Counterproductive work behaviors (CWB) threaten the well-being of organizations and their members and harm the achievement of organizational results. Thus, the objective of this study was to investigate the moderating role of ethical climate in the relationship between task conflict and CWB. A sample of 268 Brazilian workers responded to the scales of task conflict, ethical climate (benevolent, principles and rules, and independence and instrumentalism) and CWB (abuse, sabotage and production deviance, withdrawal, and theft). Hierarchical multiple regression showed that task conflict had a moderate positive correlation. Moderation was significant only to the climate of independence and instrumentalism, which became the relationship between task conflict and CWB of abuse stronger; and for the climate of principles and rules, which has become the relationship between task conflict and CWB of sabotage and deviation of production weaker. The results suggest that in a context of task conflict, climate management assumes greater relevance.